ANALISIS TATA KELOLA SERVICE DESIGN PERUSAHAAN STARTUP MENGGUNAKAN FRAMEWORK ITIL V3 - Yunianto Purnomo; Honni Honni; Yanthi Carolina; Francka Sakti Lee; Byron Harnope; Kevin Tanuwidjaya (ISTEK WIDURI, 2026)
Information technology plays a strategic role in supporting business sustainability and enhancing value creation in startup companies. To ensure optimal service quality, structured and standardized IT service governance is required, one of which can be implemented using the ITIL V3 framework. The Service Design domain in ITIL V3 focuses on designing IT services, including infrastructure, architecture, processes, and policies that support service quality. This study aims to analyze IT service governance within the Service Design domain in a startup company, with a specific focus on the Capacity Management subdomain. This research adopts a qualitative case study approach, with data collected through semi-structured interviews involving relevant stakeholders. Data analysis is conducted by comparing the existing organizational practices with ITIL V3 best practices using a gap analysis method. The results indicate that the implementation of Capacity Management has not been fully optimized, particularly in terms of capacity planning, performance monitoring, and process documentation. This study provides strategic recommendations to improve alignment with ITIL V3 standards, thereby enhancing IT service quality and operational efficiency in startup environments.